High‐Resolution Single Nucleotide Polymorphism Genotyping Reveals a Significant Problem among Breeder Resources. Issue 1 (1st March 2013) - Lucas, Mitchell R.; Huynh, Bao‐Lam; Ehlers, Jeffery D.; Roberts, Philip A.; Close, Timothy J.
Abstract : The logistics associated with a modern breeding program can be complex, relying on accuracy and communication between plant breeders, pathologists, quantitative geneticists, and support staff. International and academic facets may bring additional challenges to already error prone activities including the development, maintenance, and distribution of lines. Furthermore, practices such as bulking of seed and the maintenance of within‐accession variation among landraces must be considered when pursuing marker‐assisted approaches to breeding.